2015
DOI: 10.3122/jabfm.2015.06.150044
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Emergency Department Patients to Primary Care

Abstract: Background: Inappropriate emergency department (ED) use among Medicaid enrollees is considered a problem because of cost. We developed and evaluated a system change innovation designed to remove system barriers to primary care access for Medicaid patients.Methods: Patients who presented to the ED without an identified primary care provider were randomized to the intervention (n ‫؍‬ 72) or comparison group (n ‫؍‬ 68) for a 12-month study designed to connect these patients to primary care offices. Evaluation was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 22 publications
0
8
0
2
Order By: Relevance
“…Accessing well-established PHC reduces ED’s visits by approximately 50% and referrals to specialty care by 30% [22]. Lack of regular access to PCPs is one of the reasons for ED overcrowding worldwide [23, 24]. An international study conducted by van den Berg et al to investigate how the likelihood of attending an ED is related to accessibility of primary care showed the percentages of participants not having PCP in the following countries: 7.8% in Denmark, 10.7% in Belgium, 16.6% in Finland, 20.5% in England, 23.8% in Australia, 25.7% in Canada, 29% in Germany, 41% in Norway and Slovenia, 51.9% in Czech Republic, and 73.6% in Slovakia [25].…”
Section: Discussionmentioning
confidence: 99%
“…Accessing well-established PHC reduces ED’s visits by approximately 50% and referrals to specialty care by 30% [22]. Lack of regular access to PCPs is one of the reasons for ED overcrowding worldwide [23, 24]. An international study conducted by van den Berg et al to investigate how the likelihood of attending an ED is related to accessibility of primary care showed the percentages of participants not having PCP in the following countries: 7.8% in Denmark, 10.7% in Belgium, 16.6% in Finland, 20.5% in England, 23.8% in Australia, 25.7% in Canada, 29% in Germany, 41% in Norway and Slovenia, 51.9% in Czech Republic, and 73.6% in Slovakia [25].…”
Section: Discussionmentioning
confidence: 99%
“…15,34 The non-significant reduction in ED use found in this study underscores the mixed evidence in the literature. At least seven prior studies 12,13,[35][36][37][38][39] showed ED use reductions following a CM or similar intervention, while five studies 9,11,14,40,41 did not. In terms of study design, sample size and intervention (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…10 One intervention study conducted in the United States, the objective of which was to integrate patients cared for by emergency services into PHC services, identified the main barriers preventing patients from seeking PHC care as including a lack of transportation and difficulties in leaving children under someone's else responsibility. 14 In England, fragmentation that still exists in the health system doubles the effort and difficulties patients have to face to go through the network efficiently. Additionally, the different names of services cause confusion, so patients do not have their needs met the first time because they do not go to the right place, consequently do not receive care from professionals with the right abilities in the first consultation.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for the difficulties include the PHC units' reduced working hours, which hinders the access of the working population, and the fact that UPAs have access to resources with greater technology so that patients do not have to commute to other services in the network. 14,16 Data collected from the reports provided by the Infosaúde system did not enable the researchers to assess the hours those patients classified as being intercurrences or outpatients were served. Identifying the times care was provided, whether patients visited the service at night or during weekends or holidays, would confirm whether UPAs serve as a backup for PHC services.…”
Section: Discussionmentioning
confidence: 99%